POPULATION STRUCTURE Nerita articulata (GASTROPODA) IN THE INTERTIDAL ZONE OF TELUK LANCAR VILLAGE BENGKALIS DISTRICT RIAU PROVINCE - Ramadila, Hana; Nasution, Syafruddin; Zulkifli, Zulkifli (Asian Journal of Aquatic Sciences, 2024)
The population structure is a collection of organisms living in a particular area at a specific time and originating from the same species. The intertidal zone is between the sea's high and low tide lines, which have extreme ecological conditions. Several groups of organisms, including gastropods, can adapt to this environment. One type of gastropod that inhabits this area is Nerita articulata. This research was conducted in December 2023 in the intertidal zone of Teluk Lancar Village. The study aimed to analyze the population structure of N. articulata in the intertidal zone of Teluk Lancar Village, including population abundance, shell size frequency distribution, and distribution patterns. The research used a survey method. The intertidal zone is divided into three subzones: upper, middle, and lower. In each subzone, three quadrat plots measuring 1x1 m are placed. Environmental parameters measured include water quality, such as temperature, salinity, pH, substrate type, and organic matter. The research results indicate that the population abundance of this species varies, ranging from high to moderate to low. The highest abundance is found in the upper subzone, while the lowest is in the lower subzone. The shell sizes of this species are grouped into 3 size classes: <18.3 mm, 18.3-24.4 mm, and >24.4 mm. The largest and smallest shell sizes are commonly found in the upper subzone. The distribution pattern is uniform with a Morisita index value (Id < 1). The abundance of N. articulata among subzones differs significantly (p < 0,05), while the size among subzones does not differ significantly (p > 0,05).